ANALYSIS OF MEDIA PUBLICATIONS ON THE FUKUSHIMA NUCLEAR POWER PLANT ACCIDENT - I. A. Zykova; Yu. A. Garbuz; S. A. Zelentsova; O. B. Romanova (Радиационная гигиена)
The analysis of informing the public about radiation and radiation risks is made on the basiс of publications on the Fukushima nuclear accident after the earthquake and tsunami of March 11, 2011, by five newspapers and the official internet sites of the Federal Service for Surveillance on Consumer Rights Protection and Human Well-being and the Federal Service for Hydrometeorology and Environmental Monitoring. The analysis of the data suggests that the population is satisfied with its request in timely, clear, and reliable information on the radiation situation, protective measures and forecast of the situation development in the future. The possibility to learn about different viewpoints positively affects the mood of readers and reduces their anxiety. However, it should be recognized that, if the information have been provided by a single media only, the population would not have adequate understanding of the situation related to the accident at the Fukushima nuclear power plant.